Frontier forts of Iowa : Indians, traders, and soldiers, 1682-1862 - Whittaker, William E., 1971- (Bur oak book., 2009)
At least fifty-six frontier forts once stood in, or within view of, what is now the state of Iowa. The earliest date to the 1680s, while the latest date to the Dakota uprising of 1862. Some were vast compounds housing hundreds of soldiers; others consisted of a few sheds built by a trader along a riverbank. Regardless of their size and function-William Whittaker and his contributors include any compound that was historically called a fort, whether stockaded or not, as well as all military installations-all sought to control and manipulate Indians to the advantage of European and American trade.